2021
DOI: 10.1101/2021.06.25.450004
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic rewiring of biological activity across genotype and lineage revealed by context-dependent functional interactions

Abstract: Coessentiality networks derived from CRISPR screens in cell lines provide a powerful framework for identifying functional modules in the cell and for inferring the role of uncharacterized genes. However, these networks integrate signal across all underlying data, and can mask strong interactions that occur in only a subset of the cell lines analyzed. Here we decipher dynamic functional interactions by identifying significant cellular contexts, primarily by oncogenic mutation, lineage, and tumor type, and disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Despite being highly related genes, NRAS and KRAS fitness effects are in fact anti-correlated (Pearson cor = −0.17) because their activating mutations occur in mutually exclusive cell lines. This presents a paradox that guilt-by-association approaches alone fail to solve, instead requiring supervised learning approaches with cell line mutation data as input ( Kim et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite being highly related genes, NRAS and KRAS fitness effects are in fact anti-correlated (Pearson cor = −0.17) because their activating mutations occur in mutually exclusive cell lines. This presents a paradox that guilt-by-association approaches alone fail to solve, instead requiring supervised learning approaches with cell line mutation data as input ( Kim et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Partial correlation can measure the similarity of two gene knockout profiles after removing the effect of a third gene, set of genes, or another vector. If the functional relationship between two genes varies across the assayed cell lines, the observed correlation can be diluted by the presence of samples in which the relationship is severed [25]. For example, consider common oncogenes KRAS and NRAS, two members of the MAP kinase signaling pathway whose mutually exclusive mutations mean they are essential in different cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4D). CPD protein is known to process pro-IGF1R into its mature form [26] and we recently showed that CPD is also involved in maturation of MET receptor protein specifically in glioma cells [25].…”
Section: Resultsmentioning
confidence: 99%
“…Partial correlation can measure the similarity of two gene knockout profiles after removing the effect of a third gene, set of genes, or other vector. If the functional relationship between two genes varies across the assayed cell lines, the observed correlation can be diluted by the presence of samples in which the relationship is severed (Kim et al, 2022b). For example, consider common oncogenes KRAS and NRAS , two members of the MAP kinase signaling pathway whose mutually exclusive mutations mean they are essential in different cell lines (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%